2021
DOI: 10.52082/jssm.2021.158
|View full text |Cite
|
Sign up to set email alerts
|

Attacking Key Performance Indicators in Soccer: Current Practice and Perceptions from the Elite to Youth Academy Level

Abstract: Key Performance Indicators (KPIs) are used to evaluate the offensive success of a soccer team (e.g. penalty box entries) or player (e.g. pass completion rate). However, knowledge transfer from research to applied practice is understudied. The current study queried practitioners (n = 145, mean ± SD age: 36 ± 9 years) from 42 countries across different roles and levels of competition (National Team Federation to Youth Academy levels) on various forms of data collection, including an explicit assessment of twelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…With the ongoing digitalization in sports, the importance and usage of data in soccer has grown constantly in the last decades [ 1 , 2 ]. In line with this development, the use of spatiotemporal tracking data for tactical game analysis is seen as a beneficial tool to produce more objective, time-efficient, and in-depth analyses [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the ongoing digitalization in sports, the importance and usage of data in soccer has grown constantly in the last decades [ 1 , 2 ]. In line with this development, the use of spatiotemporal tracking data for tactical game analysis is seen as a beneficial tool to produce more objective, time-efficient, and in-depth analyses [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as technology, beginning in the early 1980s, began to rapidly evolve, new possibilities to assess internal and external training loads during training and competition became available [ 1 ]. Today, new wireless technologies are expanding to provide simultaneous data related to biomechanical, physiological and performance variables [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coaches may design special training to increase PA above 80% critically for CB and CM positions. In addition to all these, Herold et al (2021) showed that the PA rate during training did not reflect in competitions, and the PA average was lower in matches than in training (Herold et al, 2021).…”
Section: Discussionmentioning
confidence: 99%